Negotiating Pedagogical Change: Teacher Agency and the Policy-Practice Gap in Indonesia's Merdeka Curriculum History Classrooms - Anis Rohmawati; Andy Suryadi (Universitas Negeri Semarang, 2025)
This qualitative case study critically examines challenges history teachers face implementing Indonesia’s Merdeka Curriculum at SMA Negeri 12 Semarang. Through interviews, observations, and document analysis, it explores teacher perceptions, practices, obstacles, and coping strategies. Findings indicate teachers value the curriculum’s flexibility and student-centered philosophy, yet implementation is hindered by limited understanding of new concepts, difficulty designing differentiated instruction, insufficient professional development, and inadequate resources. Teachers navigate these constraints via informal collegial sharing, self-directed learning, and gradual experimentation. The study contributes to international discourse on curriculum reform in post-colonial systems, highlighting policy innovation and teacher agency. It underscores the need for sustained, context-sensitive professional support, offering insights for policymakers and educators in the Global South.